POLITENESS PRINCIPLES USED BY STAFF DESA SUMBERSUKO KABUPATEN PROBOLINGGO - Nisa', Ayu Khotimatun; Wafa, Hosnol; Tjahyadi, Indra; Zamroni, Mohammad (Program Studi Bahasa Inggris, Universitas Panca Marga, 2024)
Language phenomena often occur in society, especially politeness. Politeness is about principle that considers whether an utterance can be said to be polite or impolite. Nowadays, politeness is a matter that must be implemented in both formal and non-formal environments, and one of them in the office environment. This study analyzes the types of polite language used by Staff Desa Sumbersuko. This research implements the politeness theory proposed by Leech which includes six maxims, namely tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. The purpose of this study is to reveal which maxim is used by the staff in serving the community every day from six maxim. The method used is descriptive qualitative to describe the phenomenon in the service room of Desa Sumbersuko. The instruments used to obtain the data were observation and recording. After the data is obtained, there are several steps to determine the data form, namely: (1) Selecting the data, (2) Classification the data based on categorize, (3) Describing the data, (3) Conclusion. The result of the study is 3 maxim were found including tact maxim, generosity maxim, and agreement maxim. In addition, 2 violations were found in the staff's speech, namely generosity maxim and sympathy maxim. The total data found is 33 data. The 33 data contain 9 data of tact maxim, 3 data of generosity maxim, 16 data of agreement maxim, 3 data of violation of generosity maxim and 2 data of violation of sympathy maxim. It can be concluded that the staff desa successfully implemented politeness by Leech in serving the community.